Mitchell's Business Cycles - Schumpter, Joseph; Mitchell, Wesley C. (Quarterly Journal of Economics, 1930)
Journal Article Mitchell's Business Cycles Get access Joseph Schumpeter Joseph Schumpeter Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 45, Issue 1, November 1930, Pages 150–172, https://doi.org/10.2307/1882530 Published: 01 November 1930